L’agenda gouvernemental de croissance saisi par l’expertise environnementale des Organisations de la société civile (OSC) de défense des forêts au Cameroun - Moïse Tchingankong Yanou (VertigO)
The study on environment and development has driven the development of a university tendency said political ecology. This tendency, which emerges in confrontation or in opposition with cultural human ecology, analyses essentially power and the fight for power in matters of management of the environment. The question of mondialization of speeches and the domination of a small number between them is therefore central. Besides, the governmental logic of public intervention contrasts with this dominant perception of environmental field. It is important now to focus our view on the associative expertise about forest to see the new environmental discourse. Such is the objective of this research on the evaluation of the environmental policy in Cameroon in the forestry zone. Going from discursive analyze in the field of policies, the policy study here reveal opposition between state and civil societies organization specialize in the protection of the forest. The opposition is focus around the problem building and controversies about the growth’s gouvernmental program and the sustainable development dispositive. The consequence is the objectivation of the trajectory of the state in action in the other context ant the daily environmental policies in the developing country